Diaphragm and preparation method and application thereof
By using polydopamine-modified MOP and polymer material to blend the electrospinned MOP molecular-grade hybrid nanofiber separator in the aqueous zinc-ion battery separator, the problem of zinc dendrites piercing the separator is solved and the stability of the battery is significantly improved performance and performance.
Patent Information
- Application Number
- CN202310963319.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-31
AI Technical Summary
During the charging and discharging process of aqueous zinc ion batteries, rough zinc dendrites are easily formed, causing the separator to be pierced, causing the battery to be short-circuited, hindering its excellent performance and industrial application.
Polydopamine-modified MOP and polymer material are blended to prepare electrospinned MOP molecular-grade hybrid nanofiber separators. Through the nanocage structure of MOP and the modification of polydopamine, the porosity, electrolyte absorption and mechanical strength of the separator are improved. .
Effectively inhibit the growth of zinc dendrites, prevent the separator from being punctured by dendrites, improve the electrochemical performance and cycle life of the battery, and significantly improve the stability of aqueous zinc ion batteries.
Smart Images

Figure HDA0004373116690000011 
Figure HDA0004373116690000021 
Figure HDA0004373116690000031
Abstract
Description
Technical Field
[0001] The present application relates to a diaphragm and a preparation method and application thereof, belonging to the field of battery materials. Background Art
[0002] In recent years, aqueous zinc-ion batteries have broad prospects for application in large-scale energy storage and smart wearables due to their high discharge capacity, good cycle performance, fast charge and discharge, low cost, easy processing, environmental friendliness, high ion conductivity, and high safety. However, during the charge and discharge process, zinc ions are repeatedly and unevenly deposited and dissolved on the surface of the metal zinc electrode, forming rough and irregular dendrites on the surface of the metal zinc. Once zinc dendrites with ultra-high Young's modulus (108GPa) are formed, the dendrites will pierce the diaphragm, causing the positive and negative electrodes in the battery to directly contact, causing the battery to short-circuit, thereby hindering the excellent performance and practical industrialization of zinc-ion batteries. The growth of zinc dendrites is one of the most difficult shortcomings to overcome in aqueous zinc-ion batteries.
[0003] So far, a lot of research has been done to inhibit dendrite formation and protect the zinc anode, such as by introducing a coating on the anode surface or adjusting the electrolyte-electrode interface to provide physical protection; adding electrolyte additives or developing new electrolyte salts to coordinate ion transport, homogenize the interfacial electric field, and induce zinc deposition, etc. However, there are relatively few studies on battery separators for stable zinc-ion batteries.
[0004] As we all know, the separator, as a component of the battery, not only allows ion transfer, but also avoids direct contact between the positive and negative electrodes. Therefore, the performance of the separator has an important influence on the overall performance of the zinc-ion battery, so the design and regulation of the separator structure and performance is expected to solve the problem of zinc dendrites generated during the operation of zinc-ion batteries. At present, zinc-ion batteries mainly use glass fiber (GF) separators with a thickness of several hundred microns because of its good compatibility with aqueous electrolytes and high ionic conductivity. Unfortunately, its poor mechanical properties and large pore size make it easy to be pierced by dendrites, resulting in battery short circuit. Summary of the invention
[0005] One of the purposes of this application is to prepare a MOP molecular-level hybrid nanofiber membrane by blending MOP modified with a polymer material. The smaller crystal size (10-30 nm) of MOP provides a favorable condition for its dispersion in the polymer; polydopamine modification can prevent the agglomeration of MOP crystals and, at the same time, act as an interface adhesive to repair the gap between the polymer and MOP, promoting the hybridization of MOP crystals and polymers at the molecular level.
[0006] The second object of the present application is to provide an electrospun MOP molecular hybrid nanofiber membrane, which is prepared by the preparation method described in the first object, and is composed of a polymer matrix and polydopamine-modified MOP (MOP). The membrane has a thickness of 10 to 100 μm, and the MOP crystal size is 10 to 30 nm.
[0007] The third purpose of the present application is to provide an application of an electrospun MOP molecular-level hybrid nanofiber membrane, wherein the electrospun MOP molecular-level hybrid nanofiber membrane is the membrane described in the second purpose and is applied to aqueous zinc-ion batteries.
[0008] According to one aspect of the present application, a diaphragm is provided, wherein the diaphragm is obtained by spinning a spinning solution containing a polymer and a polydopamine-modified MOP crystal;
[0009] The thickness of the separator is 10-100 μm.
[0010] The size of the polydopamine-modified MOP crystal is 10-30 nm.
[0011] According to another aspect of the present application, a method for preparing the above-mentioned diaphragm is provided, comprising the following steps:
[0012] The polymer, the MOP crystal modified by polydopamine and the polar solvent are mixed to obtain a spinning solution, the electrospinning solution is added into a syringe, electrospinning is performed at a proper voltage, receiving distance and extrusion speed, and the membrane is obtained by drying and hot pressing.
[0013] The polymer is selected from at least one of polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyurethane and polycaprolactone;
[0014] The polar solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and tetrahydrofuran;
[0015] In the spinning solution, the concentration of the polymer is 8 to 20 wt%;
[0016] In the spinning solution, the mass of the polydopamine-modified MOP crystals is 5 to 30 wt % of the mass of the polymer.
[0017] The voltage of the electrospinning is 15-30 kV;
[0018] Extrusion speed is 1.5~3ml / h;
[0019] The receiving distance is 8 to 25 cm.
[0020] The drying temperature is 80-120°C;
[0021] The drying is carried out under vacuum;
[0022] The temperature of the hot pressing is 80-120°C;
[0023] The hot pressing pressure is 5 to 15 MPa;
[0024] The heat pressing time is 3 to 15 minutes.
[0025] The polydopamine-modified MOP crystals are obtained by the following steps:
[0026] The MOP crystals are immersed in a buffer solution containing dopamine hydrochloride, stirred at 30-60° C. for 24-72 hours, and the product is separated by centrifugation. The obtained product is washed with deionized water, freeze-dried, and the polydopamine-modified MOP crystals are obtained.
[0027] The buffer solution is a tris(hydroxymethyl)aminomethane solution with a pH of 7 to 12;
[0028] The solid-to-liquid ratio of the MOP crystals to the buffer solution containing dopamine hydrochloride is 10 to 100 g / L;
[0029] The concentration of dopamine hydrochloride in the buffer solution containing dopamine hydrochloride is 0.1-5 g / L.
[0030] MOP crystals are obtained by the following steps:
[0031] The metal salt and the organic ligand are added to the solvent respectively, mixed evenly after being fully dissolved and placed in a dark and dry place to react for one day, washed and dried to obtain MOP crystals.
[0032] The metal salt is at least one selected from zinc chloride, zinc nitrate hexahydrate, cupric chloride, cupric acetate, zirconium nitrate pentahydrate, and zirconocene dichloride;
[0033] The organic ligand is selected from one of 2-methylimidazole, 5-hydroxyisophthalic acid, 1,3,5-triimidazolylbenzene and 5-aminoisophthalic acid;
[0034] The solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, tetrahydrofuran, methanol and water.
[0035] The usage ratio of the metal salt to the solvent is (0.1-2) mol / L.
[0036] The usage ratio of the organic ligand to the solvent is (0.5-2) mol / L.
[0037] According to another aspect of the present application, a diaphragm as described above is provided for use in an aqueous zinc ion battery.
[0038] The electrospun MOP molecular-level hybrid nanofiber diaphragm has higher porosity, electrolyte absorption rate and hydrophilicity, can bind a large number of water molecules, and is beneficial to reducing the corrosion of the zinc negative electrode due to contact with the aqueous electrolyte; and has extremely high mechanical strength, can induce uniform deposition of zinc ions, thereby effectively inhibiting the growth of zinc dendrites, preventing the diaphragm from being punctured by dendrites, and improving the electrochemical performance and cycle life of the aqueous zinc ion battery as a whole.
[0039] Compared with the prior art, the electrospun MOP molecular-level hybrid nanofiber membrane provided by the present application has the following advantages:
[0040] (1) In the present application, polydopamine-modified MOP is introduced into a polymer for blending. The smaller crystal size (10-30 nm) of MOP provides a favorable condition for its dispersion in the polymer. Polydopamine modification can prevent the agglomeration of MOP crystals and at the same time act as an interfacial adhesive to repair the gap between the polymer and MOP, thereby promoting the hybridization of MOP crystals and polymer at the molecular level, thereby obtaining a MOP molecular-level hybrid nanofiber membrane.
[0041] (2) MOP crystals are rich in nanocage structures, which provide channels for ion transport.
[0042] (3) The electrospun MOP molecular-level hybrid nanofiber membrane has higher porosity, electrolyte absorption rate and hydrophilicity, and can bind a large number of water molecules, which is beneficial to reduce the corrosion of the zinc negative electrode due to contact with the aqueous electrolyte. It also has extremely high mechanical strength and can induce uniform deposition of zinc ions, thereby effectively inhibiting the growth of zinc dendrites and preventing the membrane from being pierced by dendrites, thereby improving the electrochemical performance and cycle life of aqueous zinc-ion batteries as a whole. It has great application potential in the field of aqueous zinc-ion battery membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a scanning electron microscope image of the electrospun MOP molecular-level hybrid nanofiber membrane in Example 1 of the present application, with a scale of 100 nm.
[0044] Figure 2 This is a scanning electron microscope image of the electrospun nanofiber membrane in Comparative Example 1 of the present application, with a scale of 100 nm.
[0045] Figure 3 This is a scanning electron microscope image of the commercial electrospun PAN nanofiber membrane in Comparative Example 2 of the present application, with a scale of 100 nm.
[0046] Figure 4a , b, c, d, e are the zinc-to-zinc batteries assembled with the nanofiber diaphragms in Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application at 5 mA / cm2 Polarization long cycle curve under . DETAILED DESCRIPTION
[0047] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.
[0048] Example 1
[0049] (1) Preparation of MOP: 14.87 g of zinc nitrate hexahydrate and 8.21 g of 2-methylimidazole were added to 50 ml of methanol respectively. After fully dissolved, the mixture was mixed evenly and placed in a dark and dry place to react for one day. The mixture was washed and dried to obtain MOP crystals.
[0050] (2) Polydopamine modification of MOP: 0.5 g of the above-mentioned MOP crystals were placed in 50 ml of dopamine hydrochloride buffer solution (2 g / L, pH = 9), stirred at 30°C for 24 h, and the product was separated by centrifugation. The product was washed with deionized water and freeze-dried to obtain polydopamine-modified MOP.
[0051] (3) Preparation of electrospinning solution: 1.17 g of polyacrylonitrile was added to 8 g of N,N-dimethylformamide and stirred to dissolve; 0.12 g of the above-mentioned polydopamine-modified MOP was dissolved in 2 g of N,N-dimethylformamide; the above-mentioned two solutions were mixed evenly to obtain an electrospinning solution.
[0052] (4) Preparation of MOP hybrid nanofiber membrane: The above electrospinning solution was added to a syringe and electrospun at a voltage of 25 kV, a receiving distance of 15 cm, and an extrusion speed of 2 ml / h. The composite membrane was collected, dried at 80 °C under vacuum, and hot-pressed at 100 °C and 10 MPa for 3 min to finally obtain an electrospun MOP molecular-level hybrid nanofiber membrane.
[0053] Figure 1 This is a scanning electron microscope image of the electrospun MOP molecular hybrid nanofiber membrane in Example 1 of the present application, with a scale of 100 nm. Figure 1 It can be seen that the nanofibers are uniform in size and have a high porosity in the membrane. No large particles are agglomerated in the fibers, and evenly distributed protrusions are visible on the surface of the fibers, indicating that the MOP particles are evenly wrapped inside the fibers.
[0054] Comparative Example 1
[0055] Compared with Example 1, except that polydopamine was not introduced to modify MOP, the other steps were exactly the same, and finally an electrospun nanofiber membrane with a thickness of 75 μm was obtained.
[0056] Figure 2This is a scanning electron microscope image of the electrospun nanofiber membrane in Comparative Example 1 of the present application, with a scale of 100 nm. It can be seen from the figure that the nanofibers are uniform in size and have a high porosity in the membrane, which is similar to Figure 1 In comparison, the surface of the fiber is relatively smooth.
[0057] Comparative Example 2
[0058] Comparative Example 2 is a commercial electrospun PAN nanofiber membrane with a thickness of 75 μm.
[0059] Figure 3 This is a scanning electron microscope image of the commercial electrospun PAN nanofiber membrane in comparative example 2 of the present application, with a scale of 100 nm. It can be seen from the figure that the nanofibers are uniform in size and have a high porosity in the membrane, which is similar to Figure 1 In comparison, the surface of the fiber is relatively smooth.
[0060] Comparative Example 3
[0061] Comparative Example 3 is a commercial glass cellulose film with a thickness of 220 μm.
[0062] Figure 4a , b, c, d, e are the zinc-to-zinc batteries assembled with the nanofiber diaphragms in Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application at 5 mA / cm 2 Polarization long cycle curve under .
[0063] The separators in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were cut into discs, immersed in 1M zinc sulfate for 1 minute, and excess surface water was absorbed to assemble zinc-zinc batteries. 2 The polarization stability of zinc-to-zinc batteries was tested at a current density of , and the results are shown in Figure 4. The batteries in Example 1 and Example 2 can be stably cycled for more than 1900 and 1500 hours, respectively, the battery in Comparative Example 1 short-circuited after 1100 hours of cycling, the battery in Comparative Example 2 short-circuited after 900 hours of cycling, and the battery in Comparative Example 3 short-circuited after 350 hours of cycling.
[0064] It can be seen that the stability of the electrospun nanofiber membrane and the commercial electrospun PAN membrane in the aqueous zinc ion battery of the present invention is much higher than that of the commercial glass cellulose membrane, and the stability of the electrospun MOP molecular hybrid nanofiber membrane in Examples 1 and 2 is significantly improved. This is mainly because the MOP crystal is rich in nanocage structures, which provide channels for ion transmission. At the same time, the electrospun MOP molecular hybrid nanofiber membrane has higher porosity, electrolyte absorption rate and hydrophilicity, and can bind a large number of water molecules, which is conducive to reducing the corrosion of the zinc negative electrode due to contact with the aqueous electrolyte; and it has extremely high mechanical strength, which can induce uniform deposition of zinc ions, thereby effectively inhibiting the growth of zinc dendrites and preventing the membrane from being pierced by dendrites. The electrospun MOP molecular hybrid nanofiber membrane has a higher zinc ion migration number, uniform electrolyte infiltration, and higher mechanical strength improves the ability to resist zinc dendrites, thus showing higher stability.
[0065] Example 2
[0066] (1) Preparation of MOP: 3.993 g of copper acetate and 9.11 g of 5-hydroxyisophthalic acid were added to 50 ml of water respectively. After fully dissolved, the mixture was mixed evenly and placed in a dark and dry place to react for one day. The mixture was washed and dried to obtain MOP crystals.
[0067] (2) Polydopamine modification of MOP: 2 g of the above-mentioned MOP crystals were placed in 50 ml of dopamine hydrochloride buffer solution (0.5 g / L, pH = 7), stirred at 60°C for 48 h, and the product was separated by centrifugation. The product was washed with deionized water and freeze-dried to obtain polydopamine-modified MOP.
[0068] (3) Preparation of electrospinning solution: 1.0 g of polyacrylonitrile and 0.5 g of polyurethane were added to 10 g of dimethyl sulfoxide and stirred to dissolve; 0.5 g of the above-mentioned polydopamine-modified MOP was dissolved in 5 g of N,N-dimethylformamide; the above-mentioned two solutions were mixed evenly to obtain an electrospinning solution.
[0069] (4) Preparation of MOP hybrid nanofiber membrane: The above electrospinning solution was added to a syringe and electrospinning was performed under the conditions of 20 kV voltage, receiving distance 10 cm, and extrusion speed 1.5 ml / h. The composite membrane was collected, dried under vacuum at 100°C, and hot-pressed at 100°C and 5 MPa for 12 min to finally obtain a MOP hybrid nanofiber membrane.
[0070] Example 3
[0071] (1) Preparation of MOP: 5.85 g of zirconocene dichloride and 10.87 g of 5-aminoisophthalic acid were added to 50 ml of N,N-dimethylacetamide, respectively. After fully dissolved, the mixture was mixed evenly and placed in a dark and dry place to react for one day. The mixture was washed and dried to obtain MOP crystals.
[0072] (2) Polydopamine modification of MOP: 1.5 g of the above-mentioned MOP crystals were placed in 50 ml of dopamine hydrochloride buffer solution (3 g / L, PH=10), stirred at 50°C for 72 h, and the product was separated by centrifugation. The product was washed with deionized water and freeze-dried to obtain polydopamine-modified MOP.
[0073] (3) Preparation of electrospinning solution: 0.5 g of polytetrafluoroethylene and 0.8 g of polycaprolactone were added to 8 g of N,N-dimethylformamide and stirred to dissolve; 0.25 g of the above-mentioned polydopamine-modified MOP was dissolved in 2 g of N,N-dimethylformamide; the above-mentioned two solutions were mixed evenly to obtain an electrospinning solution.
[0074] (4) Preparation of MOP hybrid nanofiber membrane: The above electrospinning solution was added to a syringe and electrospinning was performed under the conditions of 15 kV voltage, receiving distance 25 cm, and extrusion speed 2.5 ml / h. The composite membrane was collected, dried at 80 °C under vacuum, and hot-pressed at 120 °C and 5 MPa for 3 min to finally obtain a MOP hybrid nanofiber membrane.
[0075] Example 4
[0076] (1) Preparation of MOP: 4.09 g zinc chloride and 8.21 g 2-methylimidazole were added to 50 ml methanol respectively. After fully dissolved, the mixture was mixed evenly and placed in a dark and dry place to react for one day. The mixture was washed and dried to obtain MOP crystals.
[0077] (2) Polydopamine modification of MOP: 1.2 g of the above-mentioned MOP crystals were placed in 50 ml of dopamine hydrochloride buffer solution (5 g / L, pH = 12), stirred at 40°C for 48 h, and the product was separated by centrifugation. The product was washed with deionized water and freeze-dried to obtain polydopamine-modified MOP.
[0078] (3) Preparation of electrospinning solution: 1.0 g of polyacrylonitrile and 0.2 g of polytetrafluoroethylene were added to 7 g of dimethyl sulfoxide and stirred to dissolve; 0.3 g of the above-mentioned polydopamine-modified MOP was dissolved in 2 g of tetrahydrofuran; the above-mentioned two solutions were mixed evenly to obtain an electrospinning solution.
[0079] (4) Preparation of MOP hybrid nanofiber membrane: The above electrospinning solution was added to a syringe and electrospinning was performed under the conditions of 20 kV voltage, receiving distance 15 cm, and extrusion speed 1.5 ml / h. The composite membrane was collected, dried under vacuum at 100°C, and hot-pressed at 100°C and 8 MPa for 6 min to finally obtain a MOP hybrid nanofiber membrane.
[0080] Example 5
[0081] (1) Preparation of MOP: 4.63 g zirconium nitrate pentahydrate and 9.29 g 5-hydroxyisophthalic acid were added to 50 ml water respectively. After fully dissolved, the mixture was mixed evenly and placed in a dark and dry place to react for one day. The mixture was washed and dried to obtain MOP crystals.
[0082] (2) Polydopamine modification of MOP: 1.2 g of the above-mentioned MOP crystals were placed in 50 ml of dopamine hydrochloride buffer solution (0.5 g / L, pH = 7), stirred at 60°C for 48 h, and the product was separated by centrifugation. The product was washed with deionized water and freeze-dried to obtain polydopamine-modified MOP.
[0083] (3) Preparation of electrospinning solution: 1.0 g of polyacrylonitrile and 0.5 g of polyurethane were added to 10 g of dimethyl sulfoxide and stirred to dissolve; 0.5 g of the above-mentioned polydopamine-modified MOP was dissolved in 5 g of N,N-dimethylformamide; the above-mentioned two solutions were mixed evenly to obtain an electrospinning solution.
[0084] (4) Preparation of MOP hybrid nanofiber membrane: The above electrospinning solution was added to a syringe and electrospinning was performed under the conditions of 15 kV voltage, 15 cm receiving distance, and 2 ml / h extrusion speed. The composite membrane was collected, dried at 100 °C under vacuum, and hot-pressed at 80 °C and 5 MPa for 12 min to finally obtain a MOP hybrid nanofiber membrane.
[0085] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A diaphragm, characterized in that: The diaphragm is obtained by spinning a spinning solution containing a polymer and a MOP crystal modified with polydopamine; The thickness of the separator is 10 to 100 μm.
2. The diaphragm according to claim 1, characterized in that The size of the polydopamine-modified MOP crystal is 10-30 nm.
3. A method for preparing a diaphragm according to any one of claims 1 or 2, characterized in that: The following steps are involved: The polymer, the MOP crystal modified by polydopamine and the polar solvent are mixed to obtain the spinning solution, and then the solution is subjected to electrostatic spinning, drying and hot pressing to obtain the diaphragm.
4. The preparation method according to claim 3, characterized in that: The polymer is selected from at least one of polyacrylonitrile, polytetrafluoroethylene, polyvinyl alcohol, polyurethane and polycaprolactone; The polar solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and tetrahydrofuran; In the spinning solution, the concentration of the polymer is 8 to 20 wt%; In the spinning solution, the mass of the polydopamine-modified MOP crystals is 5-30wt% of the mass of the polymer.
5. The preparation method according to claim 3, characterized in that: The voltage of the electrospinning is 15-30 kV; Extrusion speed is 1.5~3ml / h; The receiving distance is 8 to 25 cm.
6. The preparation method according to claim 3, characterized in that: The drying temperature is 80-120°C; The drying is carried out under vacuum; The temperature of the hot pressing is 80-120°C; The hot pressing pressure is 5 to 15 MPa; The heat pressing time is 3 to 15 minutes.
7. The preparation method according to claim 3, characterized in that: The polydopamine-modified MOP crystals are obtained by the following steps: The MOP crystals are immersed in a buffer solution containing dopamine hydrochloride and freeze-dried to obtain the polydopamine-modified MOP crystals.
8. The preparation method according to claim 7, characterized in that: The solid-to-liquid ratio of the MOP crystals to the buffer solution containing dopamine hydrochloride is 10 to 100 g / L; The concentration of dopamine hydrochloride in the buffer solution containing dopamine hydrochloride is 0.1-5 g / L.
9. A diaphragm according to any one of claims 1 or 2, characterized in that: Used in aqueous zinc-ion batteries.
Citation Information
Patent Citations
Preparation method and application of polydopamine modified ZIF-8 functionalized nanofiber membrane
CN109577005A
MOFs / PMMA / PVDF three-phase composite battery diaphragm and preparation method thereof
CN109713198A
Nanofiber membrane and preparation method thereof
CN109957882A
Preparation method of polyhydroxyalkanoate / polydopamine composite electrospinning film and electrospinning film
CN110592947A
Nanofiber adsorbing material as well as preparation method and application thereof
CN112705171A